2016
DOI: 10.1016/j.jmig.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Versus Laparoscopic Hysterectomy for Benign Disease: A Systematic Review and Meta-Analysis of Randomized Trials

Abstract: We conducted a systematic review and meta-analysis to assess the safety and effectiveness of robotic versus laparoscopic hysterectomy in women with benign uterine disease, as determined by randomized studies. We searched MEDLINE, EMBASE, the Cochrane Library, ClinicalTrials.gov, and Controlled-Trials.com from inception to October 9th, 2014, using the intersection of the themes “robotic” and “hysterectomy.” We included only randomized and quasi-randomized controlled trials of robotic versus laparoscopic hystere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 32 publications
(69 reference statements)
5
76
1
2
Order By: Relevance
“…The demographics of our population were similar to the literature as it was reported by Albright et al (21). This meta-analysis only reported one count lower of patient with previous abdominal surgery (40–90% for Albright et al) that it could explain the difference in terms of complication that those described in our cohort (21).…”
Section: Discussionsupporting
confidence: 87%
“…The demographics of our population were similar to the literature as it was reported by Albright et al (21). This meta-analysis only reported one count lower of patient with previous abdominal surgery (40–90% for Albright et al) that it could explain the difference in terms of complication that those described in our cohort (21).…”
Section: Discussionsupporting
confidence: 87%
“…5 Albright et al recently performed a systematic review and meta-analysis of randomized trials comparing the same groups and also found similar rates of mild, moderate, and severe complications. 7 Although our analysis does show a statistically significant reduction in blood transfusion and superficial SSI rates with the robotic-assisted route compared to other MIS routes, these complications were rare and the difference may not be clinically significant. Furthermore, when a sub-analysis was performed between the specific MIS routes, increased rates of blood transfusion in the laparoscopic group appeared to be driving the overall difference compared to robotic hysterectomies.…”
Section: Commentmentioning
confidence: 52%
“…While the decrease in abdominal hysterectomy rates seen over this same time period is indeed a positive trend, 1,2 the superiority of the robotic-assisted route over other minimally-invasive surgical (MIS) routes for benign hysterectomy has yet to be proven. 37 Although cited benefits of the robotic-assisted route over conventional laparoscopy include lower estimated blood loss and shorter length of stay, complication rates appear to be similar and costs significantly higher with robotic technology. 4,812 Vaginal hysterectomy remains the preferred route when possible and is recommended as such by the American Congress of Obstetricians and Gynecologists.…”
Section: Introductionmentioning
confidence: 99%
“…5 Albright et al recently performed a systematic review and metaanalysis of randomized trials comparing the same groups and also found similar rates of mild, moderate, and severe complications. 7 Although our analysis does show a statistically significant reduction in blood transfusion and superficial SSI rates with the robotic-assisted route compared to other MIS routes, these complications were rare and the difference may not be clinically significant. Furthermore, when a sub-analysis was performed between the specific MIS routes, increased rates of blood transfusion in the laparoscopic group appeared to be driving the overall difference compared to robotic hysterectomies.…”
Section: Commentmentioning
confidence: 52%
“…While the decrease in abdominal hysterectomy rates seen over this same time period is indeed a positive trend, 1,2 the superiority of the robotic-assisted route over other minimally-invasive surgical (MIS) routes for benign hysterectomy has yet to be proven. [3][4][5][6][7] Although cited benefits of the robotic-assisted route over conventional laparoscopy include lower estimated blood loss and shorter length of stay, complication rates appear to be similar and costs significantly higher with robotic technology. 4,[8][9][10][11][12] Vaginal hysterectomy remains the preferred route when possible and is recommended as such by the American Congress of Obstetricians and Gynecologists.…”
Section: Introductionmentioning
confidence: 99%